Przyczyny oraz przebieg procesu zmian politycznych w Egipcie w latach 2011–2014 - Osiewicz, Przemysław (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2015)
Proces zmian politycznych w Egipcie po 2011 roku zyskał szczególne znaczenie w ramach szerszego procesu zmian w ramach świata arabskiego – tak zwanej arabskiej wiosny. Kairski plac Tahrir stał się najważniejszym symbolem zmian nie tylko w wymiarze wewnętrznym, ale także regionalnym. Sukces Egipcjan stał się źródłem inspiracji dla innych arabskich społeczeństw, rządzonych przez autorytarnych przywódców, na przykład, w Syrii, Jemenie, Libii i Bahrajnie. W tym kontekście ważna jest odpowiedź na pytanie, jakie czynniki społeczne, polityczne i ekonomiczne doprowadziły do tak nagłej zmiany politycznej w Egipcie. Ponadto, czy doszło do rzeczywistej wymiany elity rządzącej, czy też wydarzenia z 2011 roku były w dużej mierze inspirowane przez najbliższe otoczenie prezydenta Hosni Mubaraka i tym samym stanowiły jedynie przejaw wewnętrznej rywalizacji w ramach armii oraz reżimowej Partii Narodowo-Demokratycznej (NDP).

The political crises in Egypt in 2011 and 2013 constituted an essential element in the entire process of socio-political transformations in the Arab states of North Africa and the Middle East. The ousting of the influential President Hosni Mubarak in February 2011 had a special and symbolic meaning for both Egyptians and the citizens of other Arab states. Therefore, the victory of the demonstrators in Tahrir Square was significant in both its domestic and regional dimensions. The Egyptian success provided a clear incentive for the societies of other authoritarian Arab states, such as Syria, Libya and Yemen. In this context, it is crucial to answer the question of what social, political and economic factors brought about such a rapid political change in Egypt. From the point of view of 2015, is it really true that the ruling elite was replaced, or were the 2011 events largely inspired by circles close to President Mubarak, thereby being only a manifestation of internal competition inside the army and the National Democratic Party belonging to the regime?
The causes and course of the political transformation in Egypt in 2011–2014
Keywords: Egipt; arabska wiosna; egipska rewolucja; plac Tahrir; Kefaya; Egypt; Arab Spring; Egyptian revolution; Tahrir Square; Kefaya